Smartphone application-based addiction scale: psychometric evidence across nine Asian regions using advanced analytic methods - Chen, I-Hua; Pramukti, Iqbal; Gan, Wan Ying; Ruckwongpatr, Kamolthip; Pham, Le An; Huang, Po-Ching; Mamun, Mohammed A.; Ullah, Irfan; Jahrami, Haitham A.; Lin, Chung-Ying; Pakpour, Amir H. (John Wiley and Sons, 2024)
Introduction: A smartphone is a device with various functions, including wifi, application functions, mobile networks, ease of mobility, and the capability of using mobile data. Because of the aforementioned functions, people may use smartphones frequently. The Smartphone Application-Based Addiction Scale (SABAS) is a six-item questionnaire assessing smartphone addiction with promising psychometric properties. However, it is unclear if the SABAS possesses the strong psychometric properties across Asian regions. The present study aimed to examine the factor structure of the SABAS across nine Asian regions. Methods: Using datasets collected from Asian regions of Bangladesh, China, Indonesia, Iran, Malaysia, Pakistan, Taiwan, Thailand, and Vietnam, data from 10,397 participants (mean age = 22.40 years; 44.8% men) were used for analyses. All participants completed the SABAS using an online survey or paper-and-pencil mode. Results: Findings from confirmatory factor analysis, Rasch analysis, and network analysis all indicate a one-factor structure for the SABAS. Moreover, the one-factor structure of the SABAS was measurement invariant across age (21 years or less vs. above 21 years) and gender (men vs. women) in metric, scalar, and strict invariance. The one-factor structure was invariant across regions in metric but not scalar or strict invariance. Conclusion: The present study findings showed that the SABAS possesses a one-factor structure across nine Asian regions; however, noninvariant findings in scalar and strict levels indicate that people in the nine Asian regions may interpret the importance of each SABAS item differently. Age group and gender group comparisons are comparable because of the invariance evidence for the SABAS found in the present study. However, cautions should be made when comparing SABAS scores across Asian regions.